College Students' Responses to Suicidal Content on Social Networking Sites: An Examination Using a Simulated Facebook Newsfeed. Issue 5 (21st March 2016) - Corbitt‐Hall, Darcy J.; Gauthier, Jami M.; Davis, Margaret T.; Witte, Tracy K.
Abstract : Although Facebook has a peer‐initiated suicide prevention protocol, little is known about users' abilities to notice, recognize, and appropriately interpret suicidal content or about their willingness to intervene. In this study, 468 college students were randomly assigned to interact with a simulated Facebook newsfeed containing content reflecting various suicide risk levels. A larger proportion of those exposed to content reflecting moderate and severe suicide risk noticed, recognized, appropriately interpreted, and endorsed taking action to intervene, as compared to those exposed to content representing no or low risk. Overall, results indicate that college students are responsive to suicidal content on Facebook.